Health and Hospital Management Education in India - Kavya Sharma; Sanjay Zodpey (Indian Association of Preventive and Social Medicine, 2011)
Public health has been of national and international concern as in the process of assuring the health standards of any nation, it involves mobilizing and engaging local, state, national and international resources. Since the health problems and issues vary from country to country, the health policies and reforms addressing these should also be customized. To effectively implement and practice these developments, it is necessary to scientifically derive the lessons learnt and relate them to adequately trained and adroit health workforce. Winslow in his definition of Public Health stated, "Public Health is the science and art of preventing disease, prolonging life and promoting health and efficiency through organized community efforts for the sanitation of environment, the control of community infections, the education of individuals in principles of hygiene, the organization of medical and nursing services for the early diagnosis and preventive treatment of disease and the development of social machinery which will ensure to every individual in the community a standard of living adequate for maintenance of health, so organizing these benefits as to enable every citizen to realize his birth right of health and longevity(1). To effectively comply with the multidisciplinary dimensions reflected in Winslow's definition, it is necessary to explore the different domains of public health and provide sufficient capacity building initiatives to work upon the existing situations related to each of these domains. Public health education and competencies at various levels needed to translate evidence into policies, and to design, implement and evaluate programs(2). The reach of public health has now burgeoned from studying infectious and tropical diseases to understanding the health systems and workforce at large.........